Pengaruh Kualitas Pelayanan, Customer Relationship Management (CRM) dan Brand Image Terhadap Keputusan Konsumen Menggunakan Jasa Ekspedisi JNE Counter Berkah, Semarang - Mutia, Yunna; Febryantahanuji, Febryantahanuji; Wahyuning, Sri (Economic Reviews Journal, 2025)
This study aims to analyze the influence of service quality, customer relationship management (CRM), and brand image on consumer decisions in using the delivery services of JNE Counter Berkah in Semarang City. This research employs a quantitative approach with a survey method. The population consists of all consumers who have used the services of JNE Counter Berkah, with a total sample of 100 respondents determined through questionnaires, literature review, and observation. Data were collected using questionnaires and analyzed through descriptive and inductive analysis.The results of the study indicate that both partially and simultaneously, service quality, CRM, and brand image have a positive and significant effect on consumer decisions. Among these three variables, service quality has the most dominant influence on consumer decisions in choosing JNE Counter Berkah’s delivery services. These findings suggest that improving service quality, maintaining good customer relationships, and strengthening brand image can enhance consumer purchasing decisions.